Deciphering the growth stage specific bioactive diversity patterns in Murraya koenigii (L.) Spreng. using multivariate data analysis - Verma, Reetu; Singh, Nageswer; Tomar, Maharishi; Bhardwaj, Rakesh; Deb, Dibyendu; Rana, Anita (Frontiers in Plant Science, 2022)
The study was undertaken to characterize the total phenolics, flavonoids, essential oils, quinones, tannins and antioxidant activity of 15 samples of wild Murraya koenigii (L.) Spreng. (MK) leaves obtained from different locations of Himachal Pradesh at various growth stages. The results indicated a significant variation in total phenolic content which ranged from [(170.09 ± 4.59 to 303.57 ± 7.94) in pre-flowering, (266.48 ± 7.49 to 450.01 ± 11.78) in the flowering stage, and (212.72 ± 5.37 to 363.85 ± 9.79) in fruiting stage], expressed as mg tannic acid equivalents (TAE)/g. The total flavonoid content ranged from [(15.17 ± 0.36 to 33.40 ± 0.81) in pre-flowering, (25.16 ± 0.67 to 58.17 ± 1.52) in flowering stage, and (17.54 ± 0.42 to 37.34 ± 0.97) in fruiting stage], expressed as mg catechin equivalent (CE)/g. Total tannin content ranged from [(75.75 ± 1.69 to 143 ± 3.74) in pre-flowering, (116 ± 3.26 to 207 ± 5.42) in the flowering stage, and (47 ± 1.18 to 156 ± 4.05) in fruiting stage], expressed as mg TAE/g. The essential oil content ranged from (0.64 ± 0.01 to 0.89 ± 0.02%) in pre-flowering, (0.85 ± 0.02 to 1 ± 0.02%) in flowering stage, and (0.54 ± 0.01 to 0.7 ± 0.01%) in fruiting stage. Quinones ranged from [(2.05 ± 0.05 to 2.97 ± 0.07) in pre-flowering, (3.07 ± 0.07 to 4.95 ± 0.13) in flowering stage, and (1.02 ± 0.02 to 1.96 ± 0.04) in fruiting stage], expressed as mM/min/g tissue. Antioxidant activity ranged from [(4.01 ± 0.09 to 7.42 ± 0.17) in pre-flowering, (8.08 ± 0.19 to 13.60 ± 0.35) in flowering stage, and (3.11 ± 0.06 to 6.37 ± 0.15) in fruiting stage], expressed as μg/ml. Data was subjected to multivariate analysis using principal component analysis (PCA), hierarchical clustering analysis (HCA). This was used for elucidating the intricate relationships between the phytochemical properties. All evaluated phytochemical parameters significantly increased during the growth transition from pre-flowering to the flowering stage, followed by their gradual decrease during the fruiting stage. The present study can serve as rationale for commercializing MK for aromatic and phytopharmaceutical industries.